2012
DOI: 10.1074/jbc.m111.317982
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Indole Prenyltransferases

Abstract: Background: Known indole prenyltransferases catalyzed regioselective prenylations at N-1, C-2, C-3, C-4, C-6, and C-7 of the indole ring. Results: Recombinant 5-DMATS was assayed with tryptophan and derivatives in the presence of DMAPP. Conclusion: 5-DMATS prenylated indole derivatives at C-5. Significance: 5-DMATS fills the last prenylation gap of indole derivatives and could be used as a potential catalyst for chemoenzymatic synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 55 publications
(77 reference statements)
1
69
0
2
Order By: Relevance
“…The 1 H NMR spectra of 1 b-3 b clearly differed from those of the enzyme products of 5-DMATS with 1 a-3 a (coupling pattern and chemical shifts), [11] thus indicating prenylation at C-6. Furthermore, the 1 H NMR spectra of 1 b and 2 b corresponded well to those of the enzyme products of IptA with 1 a and 2 a.…”
Section: Confirmation Of the Prenylation Position Of The Enzyme Productsmentioning
confidence: 93%
See 3 more Smart Citations
“…The 1 H NMR spectra of 1 b-3 b clearly differed from those of the enzyme products of 5-DMATS with 1 a-3 a (coupling pattern and chemical shifts), [11] thus indicating prenylation at C-6. Furthermore, the 1 H NMR spectra of 1 b and 2 b corresponded well to those of the enzyme products of IptA with 1 a and 2 a.…”
Section: Confirmation Of the Prenylation Position Of The Enzyme Productsmentioning
confidence: 93%
“…To confirm prenylation and determine the prenylation position, seven enzyme products (1 b-7 b) were isolated by HPLC from incubation mixtures of SAML0654 with 1 a-7 a in the presence of DMAPP and subjected to MS and NMR analyses (Tables S3-S4 ) confirmed the attachment of a regular dimethylallyl moiety to a C atom. [9,11,16,17] Comparison of the NMR spectra of 1 b-7 b with those of 1 a-7 a revealed the disappearance of signals for one aromatic proton, thus proving the attachment of the prenyl moiety at the indole ring. The singlet at d H = 7.08-7.15 ppm for H-2 in all the spectra indicated that prenylation did not take place at C-2.…”
Section: Confirmation Of the Prenylation Position Of The Enzyme Productsmentioning
confidence: 94%
See 2 more Smart Citations
“…The order of the signals for the four protons of the indole ring of 1 b-6 b (that is, the two singlets between the two doublets) corresponds very well to that of the known C6-, but clearly differs from that of C5-prenylated or alkylated indole derivatives. [19][20][21] This unequivocally proves C6-geranylation of the b-series products (1 b-6 b).…”
Section: Acceptance Of Gpp By Anaptmentioning
confidence: 68%